2017
DOI: 10.1016/j.visres.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Hometown size affects the processing of naturalistic face variability

Abstract: Face exposure during development determines adults' abilities to recognize faces and the information they use to process them. Individual differences in the face categories represented in the visual environment can lead to category-specific deficits for recognizing faces that are atypical of observer's experience (e.g. the other-race effect). But what happens when observers have limited opportunities to learn about faces in general? In previous work, we found that observers from depopulated areas have poorer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Which perceptual strategies or processes may therefore underpin face and voice sorting tasks? Previous research has reported significant correlations between different measures of face sorting tasks (e.g., overall error rates, sensitivity) and the Cambridge Face Memory Test (CFMT; Balas & Saville, 2017;Short et al, 2017). These findings in conjunction with our findings could, therefore, suggest that good performance in face sorting tasks may be in fact more closely linked to the mechanisms underpinning good performance on a face learning or recognition task as opposed to a discrimination task.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Which perceptual strategies or processes may therefore underpin face and voice sorting tasks? Previous research has reported significant correlations between different measures of face sorting tasks (e.g., overall error rates, sensitivity) and the Cambridge Face Memory Test (CFMT; Balas & Saville, 2017;Short et al, 2017). These findings in conjunction with our findings could, therefore, suggest that good performance in face sorting tasks may be in fact more closely linked to the mechanisms underpinning good performance on a face learning or recognition task as opposed to a discrimination task.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies investigating the effects of within-person variability on voice and face perception have highlighted further similarities between voice and face identity processing (For voices: Lavan, Burston, & Garrido, 2019 ; Lavan, Burston, Ladwa, et al, 2019 ; Lavan, Merriman, et al, 2019 ; Stevenage et al, 2020 , For faces: Andrews et al, 2015 ; Balas & Saville, 2017 ; Jenkins et al, 2011 ; Laurence et al, 2016 ; Redfern & Benton, 2017 ; Short et al, 2017 ; Zhou & Mondloch, 2016 ). Images of faces and recordings of voices can vary considerably from instance to instance ( Burton, 2013 ; Lavan, Burton, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, aspects of the social environment may also play a role. In particular, local population density could affect the frequency of face-to-face encounters [ 29 ], and the rate at which faces are acquired across the lifespan [ 30 ]. The current estimate provides a baseline against which to assess demographic and developmental moderators.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this result, the lack of a difference in response criterion values is expected due to the instruction to sort the cards presented during the training phase into two piles. We have reported elsewhere that constraining the number of groups participants can make essentilaly freezes their response criterion within a signal detection framework (Balas & Saville, 2017;Balas & Pearson, 2017), so it is not surprising that imposing a '2-sort' task on participants fixes their response criterion near zero.…”
Section: Discussionmentioning
confidence: 99%